INTEGRASI NILAI TA’DZIM DAN DISIPLIN DALAM PEMBELAJARAN PAI MELALUI KOLABORASI PESANTREN DAN SEKOLAH FORMAL - muhamad aji abdurahman, muhamad; Wawan Hermawan; Usup Romli (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2026)
This study aims to analyze the integration of ta’dzim values (respect) and discipline in Islamic Religious Education (PAI) learning through collaboration between Islamic boarding schools (pesantren) and formal schools. The research is motivated by the decline in students’ moral attitudes and discipline in formal schools that are less influenced by pesantren culture. This study employs a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The research informants include PAI teachers, school principals, and pesantren educators who are directly involved in implementing the collaborative program. The findings indicate that the integration of ta’dzim and discipline values is carried out through structured religious habituation, strengthening manners toward teachers, exemplary behavior of ustadz, and the implementation of a point-based discipline system. The collaboration between pesantren and formal schools has succeeded in creating a holistic learning environment, encouraging the internalization of moral values, and improving students’ academic orderliness and responsibility. The application of ta’dzim values strengthens learning ethics and students’ respectful attitudes, while discipline values foster behavioral consistency in learning activities. This study concludes that the integration of ta’dzim and discipline values can be effectively implemented through systematic habituation and continuous supervision within school activities. Keywords : ta'dzim, discipline, collaboration, Islamic boarding school, school